2015
DOI: 10.1007/s00330-014-3562-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute radial nerve entrapment at the spiral groove: detection by DTI-based neurography

Abstract: • DTI-based neurography detects nerve changes during acute nerve compression. • Compression leads to a transient increase in local radial nerve FA values. • DTI provides insights into radial nerve vulnerability at the spiral groove.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…Prior investigative work has focused on the diagnostic accuracy of MR for peripheral nerve imaging [5,7,10,[17][18][19][20][21][22]. Previous impact studies in this domain are limited to a retrospective review looking at upper extremity nerve (median, radial, ulnar) abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Prior investigative work has focused on the diagnostic accuracy of MR for peripheral nerve imaging [5,7,10,[17][18][19][20][21][22]. Previous impact studies in this domain are limited to a retrospective review looking at upper extremity nerve (median, radial, ulnar) abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Im Allgemeinen erfolgt die MR-Neurographie T2-oder diffusionsbasiert. Dabeiermöglichtdie diffusionsbasierte MRNeurographie und hier insbesondere die Diffusionstensorbildgebung (DTI) auch funktionelle Aspekte von Nervenläsio-nen zu erfassen [13,22].…”
Section: Technik Der Mr-neurographieunclassified
“…Because MRIs and clinical presentation are non-invasive techniques, we believe that the addition of compartment pressure evaluation is obligatory before a definitive diagnosis is made and a fasciotomy pursued. Although there has been evidence of variance in normal compartment values, any significant rise in pressure post-exercise is highly indicative of CECS [2, 3, 6, 12, 15, 17, 19]. In fact, many other studies have concluded that the best method for diagnosing CECS is evaluation of intracompartmental pressures (ICPs) before and after exercise [2, 5, 12, 15, 17, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Borderline pressures are from 16–24 mmHg, while values above 25 mmHg are consistent with the diagnosis of CECS. Even though these values are based on the much more common presentation of CECS in the lower limb, they are used in most studies of CECS in the upper extremity [2, 3, 1517, 19]. Due to the rarity of upper extremity cases, Ardolino et al attempted to experimentally determine normal, asymptomatic, forearm pressures before and after exercise [12].…”
Section: Discussionmentioning
confidence: 99%